THE CENTRALITY OF CATTLE IN THE SOCIAL ORGANIZATION OF THE EAST POKOT PASTORALISTS OF NORTH WESTERN KENYA - Mutsotso, Beneah Manyuru; Kimaiyo, David; Gaciuki, Perpetua (European Scientific Journal, ESJ, 2014)
This paper discusses the centrality of cattle in the social organization of the East Pokot pastoralists. From early childhood, adolescence to maturity including all rites of passage, cattle is at the centre of all these practices. Relationships are conceived, maintained and dissolved over cattle. Gender relations are strongly patterned alongside cattle, hence the saying “better walk with a cow than with a woman” tells all about the position of a woman in relation of cattle in the East Pokot community. This paper seeks to explain the importance of cattle and the intensity of values and practices around cattle. The argument is that for the East Pokot, cattle is invested with certain values whose logic falls outside economic or capitalist dynamics.